Metodología para el uso de captadores de rocío. Una aproximación a una solución sostenible para el recurso hídrico en Maicao, La Guajira. (2021)
Due to the concern about the shortage of f resh wa ter in the world, especially in arid and semi-arid areas of the planet, where the main concern is the community, a project is being sought that allows an approach to dew collectors in the Municipality of Maicao , La Guajira. Which are an unconventional alternative that consists of capturing humidity, specifically the phenomenon of dew. The project developed an initial diagnosis to determine the current situation of the water resource in Maicao, reaching the conclusion that the municipality has a shortage of water.